Modern Malaysian cuisine: identity, culture, or modern-day fad? - Zainal Abidin, Muhammad Rezza; Che Ishak, Farah Adibah; Ismail, Ismi Arif; Juhari, Nurul Hanisah (Elsevier, 2020)
Malaysian cuisine presents an array of local gastronomic inventions that represent the cultural diversity and uniqueness of the national cultural heritage. However, it is difficult to gauge Malaysian cuisine based on the country's multicultural and multiracial “highly diverse” landscape due to the perplexities of each culture. These complexities have influenced the modernisation movement to revolutionise traditional Malaysian cuisine into a new invention called “Modern Malaysian Cuisine”. This review intends to reveal the ideology of modernisation in Modern Malaysian Cuisine, that is, to identify the part of the cuisine that has been “modernised” and to determine whether or not this newly invented cuisine portrays the national identity. Additionally, this review addressed the challenges of precisely defining “Modern Malaysian Cuisine”. The findings of this review can help policymakers uphold the Malaysian food identity and minimise the encroachment of other non-Malaysian cuisines in the future.